2004
DOI: 10.1016/j.susc.2004.06.159
|View full text |Cite
|
Sign up to set email alerts
|

Adsorbate induced kink formation in straight step edges on Cu(533) and Cu(221)

Abstract: Scanning tunneling microscopy (STM) and temperature programmed desorption (TPD) measurements have revealed that the straight step edges of Cu(5 3 3) surfaces are reconstructed by the room temperature adsorption of R-3-methylcyclohexanone (R-3-MCHO). STM and low energy electron diffraction (LEED) investigations have shown that the clean Cu(5 3 3) surface is composed of arrays of narrow (1 1 1) terraces separated by straight (1 0 0) steps. During room temperature adsorption of R-3-MCHO, the (1 0 0) step edges on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…A surface reconstruction of similar type was observed for (R)-3-methyl cyclohexanone adsorption on the the achiral stepped Cu{533} surface [61]. The step edges that run along the ½011 direction on the clean surface are modified into a zigzag shape upon adsorption with kinked steps running along the ½132 and ½123 directions.…”
Section: Chiral Substrate Modificationsmentioning
confidence: 54%
“…A surface reconstruction of similar type was observed for (R)-3-methyl cyclohexanone adsorption on the the achiral stepped Cu{533} surface [61]. The step edges that run along the ½011 direction on the clean surface are modified into a zigzag shape upon adsorption with kinked steps running along the ½132 and ½123 directions.…”
Section: Chiral Substrate Modificationsmentioning
confidence: 54%
“…The observation of the three well defined desorption features in the TPD spectra suggests that surface roughening results in the formation of terraces and straight step edges that are significantly wider than the single unit cell microfacets exposed by the ideal structure. Such thermal roughening has been predicted beforehand for the clean high Miller index surfaces [22] but may also be influenced by the adsorption of the (R)-3-methylcyclohexanone [12].…”
Section: Discussionmentioning
confidence: 71%
“…Any surface of a face center cubic material will be chiral provided that its Miller indices, (hkl), satisfy the constraints h = k = l = h and h Á k Á l = 0 [8]. The first such surface that was shown to be naturally chiral was Ag(643) R&S and the most thoroughly studied, naturally chiral surface is Cu(643) R&S [8][9][10][11][12][13][14][15][16][17]. These high Miller index chiral surfaces expose complex surface structures which are often described as being composed of terrace, step, and kink microfacets [18].…”
Section: Introductionmentioning
confidence: 99%
“…Alternately, it is possible that the adsorption of R-3MCHO can induce the formation of some kinks in the close-packed rows. Such adsorption induced kink formation has been observed in the case of room temperature adsorption of R-3MCHO on the Cu(221) and Cu(533) surfaces, both of which have structures based on (111) terraces separated by closepacked step edges [34].…”
Section: Coverage-dependent Desorption Of R-3mchomentioning
confidence: 65%
“…Scanning tunneling microscopy and photoemission of adsorbed Xe have been used to show that thermal roughening of the surface and of the kinked step edges, results in a distribution of adsorption sites that is significantly different from that expected on the basis of the ideal surface structure [36][37][38]. Equally importantly, it has been shown that the adsorption of R-3MCHO can also influence the distribution of sites on the surface [34]. These all suggest that while the R-3MCHO desorption spectra provide qualitative insight into the types of adsorption sites exposed by the high Miller index Cu surfaces they are of limited value in quantitative determination of site densities.…”
Section: Discussionmentioning
confidence: 99%